Abnormal semantic processing in females with fragile X‐associated tremor/ataxia syndrome. (26th December 2013) - Yang, J.‐C.; Simon, C.; Schneider, A.; Seritan, A. L.; Hamilton, L.; Hagerman, P. J.; Hagerman, R. J.; Olichney, J. M.
<x xml:space="preserve">Abstract</x> Fragile X‐associated tremor/ataxia syndrome (FXTAS), a neurodegenerative disorder, affects fragile X (FMR1) gene premutation carriers in late life. Studies have shown cognitive impairments in FXTAS including executive dysfunction, working memory and visuospatial deficits. However, less is known about cognition in females with FXTAS. Thus, we examined semantic processing and verbal memory in female FXTAS patients with event‐related potentials (ERPs) and neuropsychological testing. Sixty‐one females (34 FXTAS, Mage = 62.7; 27 controls, Mage = 60.4) were studied with 32‐channel ERPs during a category judgment task in which semantically congruous (50%) and incongruous items were repeated approximately 10–140 seconds later. N400 and P600 amplitude data were submitted to analysis of covariance. Neuropsychological testing demonstrated lower performance in verbal learning and executive function in females with FXTAS. Event‐related potential analyses showed a significant reduction of the N400 congruity effect (incongruous − congruous) in the FXTAS group. The N400 congruity effect reduction in females with FXTAS was mainly due to increased N400 amplitude to congruous new words. No significant abnormalities of the N400 repetition effect or the P600 repetition effect were found, indicating preserved implicit memory and verbal memory, respectively, in females with FXTAS. The decreased N400 congruity effect suggests abnormal semantic expectancy and/or semantic network disorganization in female FXTAS patients. The enhanced N400 amplitude to congruous new words may reflect decreased cognitive flexibility among FXTAS women, making access to less typical category exemplar words more difficult.